2020
DOI: 10.3389/fnhum.2020.00011
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Is Associated With Better Executive Function in University Students

Abstract: Introduction: In recent years, the study of the benefits that physical exercise has on brain health has acquired special relevance. In order to implement exercise as an intervention to protect the brain, it is important to have a more clear idea of its effect in the young population. However, few studies have been carried out on these ages. Objective: The main objective of our study was to evaluate the association between physical activity (PA) with memory and executive function, in university students, analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
2
24
0
1
Order By: Relevance
“…Thus, our finding complements the existing literature by showing that even in younger adult's exercise-induced changes in brain structure are an important mediator between physical fitness (e.g., CRF) and cognitive performance. Additionally, as the psychological trauma usually has negative impacts on the immunological phenotype of microglia of the frontal cortex [55], the unexpected decrease in grey matter volume in the control group may be induced by participants' stress reaction during the final examination [14,59,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our finding complements the existing literature by showing that even in younger adult's exercise-induced changes in brain structure are an important mediator between physical fitness (e.g., CRF) and cognitive performance. Additionally, as the psychological trauma usually has negative impacts on the immunological phenotype of microglia of the frontal cortex [55], the unexpected decrease in grey matter volume in the control group may be induced by participants' stress reaction during the final examination [14,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is mounting evidence in the literature indicating that higher CRF levels and regular physical exercise are associated with better cognitive performance, especially in children and older adults [ 10 , 11 ]. For example, executive control, a cognitive domain associated with “top-down” regulation of goal-directed behavior [ 12 , 13 ], is positively associated with physical exercising and CRF level in both children and older adults [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, the effects of exercise interventions in early adulthood on EC performance are not fully understood [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This period of early adulthood can be a critical time for the development of obesity as an increased body mass index (BMI) during this time is associated with higher morbidity, premature mortality, and chronic obesity [21]. As well as the health benefits of physical activity, observational studies have shown increased physical activity is linked to improved cognitive function including executive function in university students [22][23][24], improved mood, lowered stress [25], and improved working memory capacity [26]. In contrast, sedentary behaviour related to uninterrupted sitting has been shown to increase discomfort and sleepiness [27] in this population.…”
Section: Introductionmentioning
confidence: 99%
“…That is why international organizations support them and recommend that people aim for (or maintain) adequate and healthy levels of physical activity and engage in sports ( World Health Organization., 2019 ). Researchers are also paying more and more attention to how engaging in physical activity and sports is associated with other domains, such as academic performance ( St Clair-Thompson and Gathercole, 2006 ), or with positive aging ( Salas-Gomez et al, 2020 ). For older children and adolescents, doing sports may also have other important benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The latter association might be particularly important at a malleable age, such as adolescence, when an individual’s cognition and personality take shape ( Paus, 2005 ; Steinberg, 2005 ; Heckman, 2011 ; Thompson et al, 2019 ). Results of studies sustaining the hypothesis of a correlation between sports or physical activity and cognitive abilities or soft skills are mixed ( Carson et al, 2016 ; Li et al, 2017 ; Salas-Gomez et al, 2020 ), however, making it difficult to precisely estimate the strength of this association.…”
Section: Introductionmentioning
confidence: 99%